1999
DOI: 10.1038/sj.bjp.0702549
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of inducible nitric oxide synthase prevents ischaemic brain injury

Abstract: 1 The aim of this study was to investigate the e ect of N-(3-(aminomethyl)benzyl)acetamidine (1400W), a selective inhibitor of inducible calcium-independent nitric oxide synthase (iNOS), on the functional and histopathological outcomes of experimental transient focal cerebral ischaemia in rats. 2 Transient ischaemia was produced by the occlusion for 2 h of both the left middle cerebral artery and common carotid artery. Treatments with 1400W (20 mg kg 71 ) or vehicle were started 18 h after occlusion of the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(71 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…Although the exact mechanism is not known, the animal data indicate that insulin may provide protection by direct interaction with IGF-1 receptor and/or an indirect action by reducing the blood glucose levels. Although NO produced by iNOS is believed to play a role in the pathophysiology of cerebral ischemic injury (Iadecola et al, 1997;Nagayama et al, 1998;Iadecola, 1999;O'Mahony and Kendall, 1999;Parmentier et al, 1999), little information is available about the possible regulation of iNOS gene expression by glucose. This study reports that signals for upregulation of the LPS-induced expression of iNOS by glucose were mediated via C/EBP-␦.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism is not known, the animal data indicate that insulin may provide protection by direct interaction with IGF-1 receptor and/or an indirect action by reducing the blood glucose levels. Although NO produced by iNOS is believed to play a role in the pathophysiology of cerebral ischemic injury (Iadecola et al, 1997;Nagayama et al, 1998;Iadecola, 1999;O'Mahony and Kendall, 1999;Parmentier et al, 1999), little information is available about the possible regulation of iNOS gene expression by glucose. This study reports that signals for upregulation of the LPS-induced expression of iNOS by glucose were mediated via C/EBP-␦.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were cared for until 40 h after surgery, at which time the rats were treated with either saline or a bolus of 10 mg/kg of 1400W, followed by a constant infusion of 1400W (10 mg⅐kg Ϫ1 ⅐h Ϫ1 ) for 4 h before death. The dose of 1400W was determined based on evidence from the literature (4,5,24) and preliminary experiments done in our laboratory. At 44 h, rats were anesthetized with pentobarbital sodium (30 mg/kg iv), and the thorax was opened.…”
Section: Methodsmentioning
confidence: 99%
“…Use of selective nNOS antagonists (O'Neill et al, 2000) and nNOS knockout mice (Huang et al, 1994), confirmed that neuronal production of nitric oxide contributes to ischemic cell death. iNOS has been associated with oxidative stress , and modifying its activity may have therapeutic potential (Parmentier et al, 1999). However, nitric oxide may also serve as an antioxidant against products of the Fenton reaction (Chiueh, 1999).…”
Section: Nitric Oxide Synthase Inhibitionmentioning
confidence: 99%